Measurement of resilience and the time value of resilience - Ferris, Timothy L. J. (Institute of Electrical and Electronics Engineers (IEEE), 2021)
In prior work, a measure of resilience for use in systems design and management was presented. The measure has the form of a time integral of the system performance level. This form generates the research question: Is the time value of resilience a meaningful concept, like the time value of money in engineering economics. This article presents four scenarios to explore the relationship between time and the value of resilience of a product or system. The scenarios are: perishable commodity packaging, the value of resilience rapidly diminishes after the contents’ expiry; a consumer durable product for use in an evolving environment and interface requirement, where the value of resilience is related to the expiry of platform resilience capability; a national infrastructure asset, where usage increases during the system life; and a factory, where the value of resilience depends on the obsolescence of the product. In the first two and last cases, the value of resilience is high for a finite interval and then low or zero. In the third, the value of resilience increases as the asset ages
Keywords: System lifecycle management; Systems system resilience; system metric; system analysis and design; Measurement